The Role of the Mobile Brigade Unit in Protecting the Community Regarding Illegal House Evictions at the Riau Islands Police - Masdoro, Masdoro; Mashdurohatun, Anis (UNISSULA Semarang, 2025)
Procurement in the body of goods and services of the Indonesian National Police is currently carried out electronically since the enactment of Law Number 11 of 2008 concerning Electronic Information and Transactions has been given broad legal space. E-procurement as an information system is a synergy between data, data processing machines (which usually include computers, application programs, and networks) and humans to produce information. Procurement of goods/services electronically is basically aimed at: This study uses a normative legal approach method, with analytical descriptive research specifications. Secondary data comes from primary legal materials, secondary law, and tertiary law, as well as legal expert sources. Data collection through a mixed method between field data and literature. Data processing is carried out qualitatively, then conclusions are drawn using the inductive method. Research problems are analyzed using the Theory of Legal Protection, Theory of Legal Systems and Theory of Legal Certainty. The results of this study indicate that: the effectiveness of the law on procurement of goods and services in the National Police in terms of the effectiveness of its legislation by referring to the organizational perspective on government procurement of goods and services and the role of supervisory institutions on government procurement of goods and services. The data collection method was carried out by literature study with legal materials, namely laws and regulations. The analysis used was qualitative analysis seen from an empirical perspective which was used to analyze data obtained from the literature study. The results of the study are that the law governing the procurement of goods and services has not provided sufficiently strict sanctions so that violations still occur, but with the existence of e-procurement, the procurement of goods and services has become more transparent.